Simple fast light detector device based on a 1P28 photomultiplier tube - Marconi, Mario Carlo, author; Libertun, A. R., author; Sánchez, G., author; Optical Society of America, publisher (Colorado State University. Libraries, 1997)
A simple implementation of the stroboscopic optical boxcar technique for determining intensity profiles of repetitive nanoseconds light pulses is presented. The device, implemented with standard components and a 1P28 photomultiplier tube, can be used for fluorescence decay measurements with subnanosecond time resolution.